A new species of Zhangixalus (Anura: Rhacophoridae), previously confused with Zhangixalus smaragdinus (Blyth, 1852) - Yu, Guohua; Hui, Hong; Hou, Mian; Wu, Zhengjun; Rao, Dingqi; Yang, Junxing (Zootaxa, 2019)
We describe a new species of Zhangixalus from southern Yunnan of China, Vietnam, and Thailand based on morphological and molecular evidence. The new species had been confused with Zhangixalus smaragdinus (Blyth, 1852) in the past. Zhangixalus pachyproctus sp. nov. can be distinguished from Z. smaragdinus morphologically by the protruding vent in adult males, large thick grey reticular mottles below the white stripe on flank, more oblique snout in profile and wider head, longer snout, greater internarial distance, larger tympanum and longer hindlimb. The new species can be distinguished from other species of Zhangixalus with green dorsum by the following combination of characters: body size larger (SVL of adult males: 74.2–83.3 mm; SVL of adult female: 102.4 mm); dorsum smooth; narrow white stripes along edge of the lower jaw, body sides, outer side of limbs and above the vent; absence of brown bands on canthus rostralis, upper eyelid and supratympanic fold; webbing between fingers and toes complete except between the first two fingers; and internal single subgular vocal sac. Phylogeny based on comparison of 16S rRNA sequences suggests that the new species is the sister taxon to Z. smaragdinus and the two species differ by 7.63% in the uncorrected pairwise distance of 16S sequences.